PAPARAN KEBISINGAN, UMUR, MASA KERJA, DAN PEMAKAIAN APT TERHADAP AMBANG PENDENGARAN PEKERJA - Hafidah Destiani Putri; Rusmiati .; Demes Nurmayanti (GEMA LINGKUNGAN KESEHATAN, 2019)
PT. Dok dan Perkapalan Surabaya (Persero) or DPS is state-owned enterprises which is engaged in shipbuilding and nationalization from the Netherlands. PT. DPS in the operational process requires a machine that causes noise during the production process. The purpose of this study is to know the influence of noise intensity, age, working, and ear plug on hearing threshold man-workers in production section of PT. DPS.This study used observational research design and belongs to field research. Based on the time, this study belongs to cross sectional research. The sample of this study is 55 people and used random technique. The researcher collected the data from observation, interview, and measuring. The data analysis was calculated by SPSS 20 version used Chi-Square test. If p 0.05, the criterion Ho is can not be rejected and if p 0.05, Ho is rejected. The results showed that the hearing threshold of production workers at PT. DPS are abnormal at 71.4%. Workplace noise that meets the requirements is only 40.5% and it is not acceptable for the requirements. Most of the workers in the production section of PT. DPS is 40 years old, 92.9% and the rest are ≤ 40 years old. Work period of workers in the production section of PT. DPS have a working period of 10 years with 97.6%. Workers in the production section of PT. DPS that did not use APT were 69% and the rest did not use APT. The hearing threshold man-workers was influenced by the noise (p=0.041) and the use of ear plug (p=0.03) and the hearing threshold was not influenced by age (p=0.192) and working (p=0.286).It is recommended for companies to carry out technical control, implement a work shift system if the work rotation system cannot be applied optimally, provide training on ear protection devices, and provide strict supervision and policies for workers who do not use APT in noisy workplaces.  Keywords: noise, age, ear plug, hearing threshold